Cuento y lenguaje oral de los niños y niñas de la escuela de Educación Básica Particular “Semillitas” de la ciudad de Riobamba 2016. - Bonilla Echeverría, Zoila Esther (2017)
This thesis refers to: TALES AND ORAL LANGUAGE OF THE CHILDREN OF THE PARTICULAR BASIC EDUCATION SCHOOL "SEMILLITAS" OF THE RIOBAMBA CITY. This investigation work is the result of the children^ need to develop their oral language through the use of tales for this, instruments that collect information relevant to the verification of the hypothesis were applied and the establishment of conclusions and recommendations which propose solutions to the problem detected, the methods used were: Inductive-Deductive, Analytical-Synthetic and for the test of the hypothesis the method Chi (Chi) -Quadrated (X2) was used which compares the observed distribution of the data with an expected distribution of them: the technique used is direct observation using as an instrument the observation sheet, which was structured taking into account the problems derived, the use of tales as a strategy for the development of oral language in children, different types of tales were used for the development of the language and the determination of the development level of the oral language in children of 4 years old. This information allowed to tabulate, graph and interpret the results. The participating population was 32 children, not only a sample was worked, the whole population was taken into account in order to get results more reliable and the most credibility; concluding that the use of tales in the daily work with the children is necessary, because they work as indispensable strategies to develop oral language at the same time strengthen communicative skills. This proposal was presented through a workshop which the tales were used as methodological strategies divided into three units: Unit 1. - Pictographic Tales, Unit 2. - Tales with stories of teachings and Unit 3. - Tales of fantasies and adventures; these exercises will contribute to reach to development the oral language. The oral language development is one of the essential parts in children, because it allows transferring ideas, thoughts, feelings among others, being its realization very important during the first years of their life, it also determines very important aspects in the infant’s future. This is why necessary to present striking and innovative learning activities is.